Two-phase anaerobic co-digestion of dairy manure with swine manure - Zhengjun, Guan; Xianli, Sun; Lanping, Bi; Wenzhe, Li; Ying, Zhang; Zhigang, Wang (International Journal of Agricultural and Biological Engineering, 2016)
In order to solve the problems associated with high fiber content, and the ensuing lower biogas volume yield in anaerobic digestion of dairy manure, a study of the co-digestion of separated liquids from dairy manure combined with swine manure using a two-phase anaerobic digestion process was conducted. The influence of level of total solids (TS) and hydraulic retention time (HRT) of the mixed liquor on the specific methane production were studied. Three TS levels 8%, 10% and 12% were investigated. Analysis of the results show that a maximum specific methane yield of 132.99 L/kg volatile solids (VS), can be obtained with a TS of 9%, an inoculation rate of 30%, the duration of hydrolytic acidification phase of 5 d, and an HRT of the methanogenic phase of 10 d. These findings could provide directions for improving the biogas production by performing the co-digestion of dairy manure with swine manure. Keywords: co-digestion, two-phase anaerobic digestion, dairy manure, swine manure, biogas DOI: 10.3965/j.ijabe.20160902.1637 Citation: Guan Z J, Sun X L, Bi L P, Li W Z, Zhang Y, Wang Z G. Two-phase anaerobic co-digestion of dairy manure with swine manure. Int J Agric & Biol Eng, 2016; 9(2): 146－152.